Recommendations for evaluation of neurogenic bladder and bowel dysfunction after spinal cord injury and/or disease. (3rd March 2020) - Tate, Denise G.; Wheeler, Tracey; Lane, Giulia I.; Forchheimer, Martin; Anderson, Kim D.; Biering-Sorensen, Fin; Cameron, Anne P.; Santacruz, Bruno Gallo; Jakeman, Lyn B.; Kennelly, Michael J.; Kirshblum, Steve; Krassioukov, Andrei; et al.
Abstract : Objective: To provide an overview of clinical assessments and diagnostic tools, self-report measures (SRMs) and data sets used in neurogenic bladder and bowel (NBB) dysfunction and recommendations for their use with persons with spinal cord injury /disease (SCI/D). Methods: Experts in SCI/D conducted literature reviews, compiled a list of NBB related assessments and measures, reviewed their psychometric properties, discussed their use in SCI/D and issued recommendations for the National Institutes of Health (NIH), National Institute of Neurological Disorders and Stroke (NINDS) Common Data Elements (CDEs) guidelines. Results: Clinical assessments included 15 objective tests and diagnostic tools for neurogenic bladder and 12 for neurogenic bowel. Following a two-phase evaluation, eight SRMs were selected for final review with the Qualiveen and Short-Form (SF) Qualiveen and the Neurogenic Bowel Dysfunction Score (NBDS) being recommended as supplemental, highly-recommended due to their strong psychometrics and extensive use in SCI/D. Two datasets and other SRM measures were recommended as supplemental. Conclusion: There is no one single measure that can be used to assess NBB dysfunction across all clinical research studies. Clinical and diagnostic tools are here recommended based on specific medical needs of the person with SCI/D. Following the CDE for SCI studies guidelines, we recommend both the SF-Qualiveen for bladder and the NBDS for bowel as relatively short measures with strong psychometrics. Other measures are also recommended. A combination of assessment tools (objective and subjective) to be used jointly across the spectrum of care seems critical to best capture changes related to NBB and develop better treatments.